Tensile and Interfacial Performance of Epoxy Composites Reinforced with Alkali-Treated Kenaf Fibers - Mohd Razali, Muhammad Afif; Main, Nor Mazlana; Muhammad Arif Asyraf Zainuddin; Wafi Zulaikha Rozi; Marsi, Noraini (Journal of Advanced Mechanical Engineering Applications, 2026)
Natural fiber-reinforced composites are increasingly promoted as sustainable alternatives to synthetic materials in lightweight applications. This study evaluates the tensile properties of epoxy composites reinforced with long kenaf fibers (40–60 mm) treated with sodium hydroxide (NaOH). Composites containing 0%, 15%, 30%, and 45% fiber by weight were fabricated using the hand lay-up method and tested according to ASTM D3039. Morphological analysis was carried out using Scanning Electron Microscopy (SEM) and Energy Dispersive X-ray Spectroscopy (EDX). The composite with 45 wt% kenaf fibers treated with 5% NaOH showed the highest tensile strength (50.46 MPa) and strain (5.14%), with statistical significance confirmed by ANOVA (p < 0.05). In comparison, the 6% NaOH-treated composite at 30 wt% achieved the highest tensile modulus (1619.5 MPa). SEM observations indicated stronger fiber–matrix adhesion in the 5% NaOH group, while the 6% treatment caused fiber weakening and voids. EDX confirmed elemental changes on fiber surfaces after alkali treatment. Unlike many previous studies that mainly focused on short kenaf fibers and lower fiber loadings, this study examines the tensile and interfacial performance of long kenaf fibers (40–60 mm) at higher reinforcement levels up to 45 wt%. Overall, the findings indicate that moderate NaOH treatment, particularly 5% at higher fiber loadings, provides an optimal balance of strength and ductility. These results support the potential use of long kenaf fiber-reinforced epoxy composites in sustainable lightweight structural applications such as automotive and packaging components.